Ruthenium(II)‐Catalyzed Synthesis of Pyrrole‐ and Indole‐Fused Isocoumarins by C−H Bond Activation in DMF and Water. Issue 6 (2nd February 2016) - Singh, Keisham S.; Sawant, Sneha G.; Dixneuf, Pierre H.
Abstract: Pyrrole‐ and indole‐fused isocoumarins constitute important structural units in natural products and pharmacophores, although the direct and selective bifunctionalization of pyrrole and indole remain a challenge. Herein, we report a one‐pot synthesis of pyrrole‐ and indole‐fused isocoumarins from simple 1‐methylpyrrole‐2‐carboxylic acid and 1‐methylindole‐3‐carboxylic acid by annulation with alkynes in the presence of a ruthenium(II) catalyst based on [RuCl2 ( p ‐cymene)]2 with Cu(OAc)2 ⋅ H2 O as the oxidant in DMF. This ruthenium(II)‐catalyzed transformation was shown to be profitably performed in water as the solvent. The reaction, which involves carboxylate coordination, activation of the heterocyclic sp 2 C−H bond, and insertion of the alkyne, is regioselective, which leads to good yields of the isocoumarins. Abstract : Ring, ring ! 1‐Methylpyrrole‐2‐carboxylic acid and 1‐methylindole‐3‐carboxylic acid are efficiently annulated with alkynes by using the inexpensive and stable‐to‐water [RuCl2 ( p ‐cymene)]2 catalyst with Cu(OAc)2 ⋅ H2 O as the oxidant and as acetate provider by C−H and O−H bond activation to give their respective pyrrole‐ and indole‐fused isocoumarin derivatives. These catalytic reactions can be performed in DMF and competitively in water.